How Local Governance on Educational Budget Affects Access to Junior Secondary Education in Indonesia - Widarthi, Yelly; Jasmina, Thia (Jurnal Ekonomi Dan Statistik Indonesia, 2025)
Empirical studies have consistently shown that simply allocating government funds to public goods and services would not guarantee desired outcomes if the budgeting process is flawed. This study explores how local governments can optimize their education budgets to improve educational outcomes through effective governance. Specifically, it examines the impact of local government budgets on access to basic education in Indonesia, focusing on junior secondary education, which remains a critical issue. The study also takes into account the total government education budget, including both local and central government funding. Using panel data from 455 districts in Indonesia between 2017 and 2019, the results reveal that as long as budget allocations are strategically aligned with current challenges in student access, and there is consistency between planning and execution, the budget will lead to the desired outcomes. The findings suggest that education budgets will only improve access to junior secondary education when good governance is practiced throughout the budgeting process. Conversely, in districts with poor governance, the budget has little to no impact on student access.